An Investigation Into Interpersonal and Peripersonal Spaces of Chinese People for Different Directions and Genders - Yu, Xiaoqing; Xiong, Wei; Lee, Yu-Chi (Frontiers in Psychology, 2020)
This study explores the interpersonal space (IPS) and peripersonal space (PPS) of Chinese people and evaluates the relationship between the two spaces for different directions and genders. Seventy-one participants were recruited for this study. Participants were required to determine their IPS in eight directions (0°, 45°, 90°, 135°, 180°, 225°, 270°, 315°) when approached by male or female confederates in the comfort distance task. Each participant was also asked to judge their PPS in five directions (0°, 45°, 90°, 270°, 315°) following the same procedure. Results showed that their IPS was significantly influenced by direction (p < 0.05), with the largest distance in the front (0°) and the closest distance in the rear (135°, 180°, 225°), indicating noncircular IPS among Chinese subjects. Moreover, the PPS on the right side (90°) was larger than in other directions (0°, 45°, 270°, 315°). Participants maintained larger IPS than PPS in the front, but the IPS was closer than PPS on the right and left sides. When facing a female confederate, larger IPS was preferred than PPS, whereas the opposite held true when facing a male confederate. Comparison of participants’ arm length and PPS showed that the reachability distance was overestimated in the front but underestimated laterally. The findings of this study can be applied to environmental design, space utilization, and social interaction.